Land Tenure and Utilisation Challenges of The Land Bank Concept in Indonesia - Permadi, Iwan (Universitas Islam Malang, 2023)
The existence of the Land Bank is arguably redundant, as the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency could be optimised in seeking balance and justice in the distribution of land, including to indigenous peoples. Then, the model of open cooperation in land utilisation by not determining the priority scale from the Land Bank to business entities, individuals, or community groups, can open space for abuse of power and conflicts of interest. This type of research is normative juridical with a conceptual approach and a statutory approach. The results of the study show that the Government should form policies by striving to protect the livelihoods of indigenous peoples, the issuance of PP No.64 of 2021 concerning the Land Bank Agency can cause conflicts of interest between the community and the government, so the government needs to conduct a review and master the real land issues of land tenure in the Land Bank policy.